(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article explores the psychological characteristics of teenagers who are prone to committing crimes. It examines various factors such as impulsivity, aggression, low self-control, and lack of empathy that contribute to delinquent behavior in adolescents. Understanding these psychological traits can aid in the development of preventive measures and interventions for at-risk youth.